PERSEPSI SISWA TERHADAP MEDIA PEMBELAJARAN DALAM JARINGAN (Daring) PADA MATA PELAJARAN BIOLOGI DI MADRASAH ALIYAH NEGERI TARAKAN - Nurlina Nurlina; Fitri Wijarini; Aidil Adhani (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2022)
Abstract: This study aims to look at students' perceptions of online learning media in Biology subjects at MAN Tarakan. This type of research is a survey research with a qualitative descriptive method. The population in this study was 200 students with a total sample of 66 students. Overall data was obtained based on scores and answers from student perception questionnaires distributed online via Google form. The results showed that students' perceptions of the use of learning media in the network system (Online) in Biology subjects at MAN Tarakan students had good perceptions of the platform as learning media in the network system (Online) in Biology subjects. Keywords: Perception, Media, Online.